Estimates of cost-price passthrough from business survey data - Keshav Dogra; Sebastian Heise; Edward S. Knotek; Brent H. Meyer; Robert W. Rich; Raphael Schoenle; Giorgio Topa; Wilbert van der Klaauw; Wändi Bruine de Bruin (Federal Reserve Bank of New York, 2023)
We examine businesses' price-setting practices via open-ended interviews and in a quantitative survey module with business contacts from the Federal Reserve Banks of Atlanta, Cleveland, and New York in December 2022 and January 2023. Businesses indicated that their prices were strongly influenced by demand, a desire to maintain steady profit margins, and wages and labor costs. Survey respondents expected reduced growth in costs and prices of about 5 percent on average over the next year. Backwardlooking, forward-looking, and hypothetical scenarios reveal average cost-price passthrough of around 60 percent, with meaningful heterogeneity across firms.
Keywords: D4; E3; L2; 330; prices; business survey; hypothetical questions